(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. There is no objective method currently available for assessing the extraocular muscles functional status, which could be considered definitely effective and convenient for the extensive use in ophthalmological practice. Also, there is no comparative analysis of bioelectric potentials of the extraocular horizontal rectus muscles in concomitant esotropia and exotropia. The purpose of the study was to investigate the functional status of bioelectric potentials of the extraocular horizontal rectus muscles in concomitant esotropia and exotropia using surface electromyography (SEMG). Materials and methods. There were 18 children under follow-up (12.9 ± SD3.2) years of age, of which 12 (24 eyes) had concomitant esotropia and 6 (12 eyes) with concomitant exotropia, and healthy children (28) of the same age. Horizontal muscle functional status was determined by computer myograph M-TEST-2. Results. The frequency in esotropia of bioelectric potentials of the internal rectus muscle is much higher than the frequency of the extraocular rectus muscle (128 Hz ± 19.35 and 60.9 ± 16.7 Hz, respectively, p = 0.0003). The frequency in exotropia of bioelectric potentials of the extraocular rectus muscles was in average higher than the frequency of the intraocular rectus muscle (109 ± 9.9 Hz and 55.0 ± 1.57, respectively, p = 0.004). The frequency response when compared in healthy children showed no differences between the internal and external line (63.0 ± 19.9 Hz and 63.7 ± 21.1 Hz, p> 0.05). Conclusions. 1. The results suggest that the children with concomitant strabismus have functional disorders of the horizontal rectus muscles, as evidenced by SEMG data. 2. It was established that the bioelectric potentials frequency of the intraocular rectus muscle in esotropia and extraocular rectus muscle in exotropia is higher than the frequency of the relevant muscles in the healthy children. 3. The bioelectric potential of the intraocular and extraocular rectus muscles in the healthy children does not differ, and in children with concomitant esotropia and exotropia differs significantly.